Investasi dalam Perspektif Hadis - Abdul Rozikin Japar Sodik; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Investment activities in the modernization era are an economic activity that is of great interest to society, especially young people, whose development is very vulnerable to general macroeconomic conditions. And to secure the money and to maintain economic stability, especially now that inflation is very large which has an impact on economic stability. This research aims to discuss saving from a hadith perspective. The formal object of this research is the understanding and urgency of investment which is formulated based on hadith themes. The material object of this research is an investment case within the theoretical framework of investment from a hadith perspective. The results of this research show that hadith themes can be formulated within the theoretical framework of investment from a hadith perspective. The discussion of this research explains that investment is relevant to economic aspects, financial aspects and the influence of a person which includes and explores information, exploration of something he feels he needs. This research data was obtained from various sources, namely the Indonesian Stock Exchange website, Bank Indonesia, Central Statistics Agency (BPS) and Digital Hadith. The conclusion of this research is that the theoretical behavior of investment can have positive and negative impacts as well as the implementation of investment in life which is formulated in the hadith thematic framework in line with the era of modernization.